A brief analysis of project-based learning in STEM for developing engineering competencies of undergraduate students - Syzdykova, R.N. (Recent Contributions to Physics, 2025)
Project-based learning has become a key pedagogical approach in STEM education, particularly in preparing engineering students to tackle complex, real-world problems. This review presents a brief analysis of recent international studies published between 2019 and 2026 on the implementation of project-based learning in STEM higher education. The selected literature is examined in terms of research methodology, instructional design, and educational outcomes. The analysis reveals that most empirical studies employ mixed methods or quasi-experimental designs and consistently demonstrate positive impacts of project-based learning on students' engineering competencies, problem-solving skills, motivation, and interdisciplinary thinking. Particular challenges include assessing learning outcomes, integrating interdisciplinary content, and using digital and laboratory-based learning environments. By systematizing key findings and identifying prevailing research trends, this review highlights the need for greater terminological consistency and methodological alignment in future research. The results can serve as a basis for curriculum development and promote the effective integration of project-based learning strategies in engineering and STEM education.
Keywords: рroject-based learning; STEM education; literary analysis